A tale of one home, one fence, and one bridge: Roma and non-Roma perspectives. Issue 1 (1st June 2021) - WITKOWSKI, MACIEJ; NOWICKA, EWA
Abstract : In this article, the authors unveil the social context surrounding a publicly funded project to improve the extremely poor housing conditions of a Roma community in Poland. The focus was on one Carpathian mountain village in which a Bergitka Roma settlement has existed for more than 80 years. A brand-new apartment house for the local Roma minority partly replaced the earlier settlement in a village populated by Górale, a highlander group that is the local majority. At present about 70 Roma live in the new building. The ethnographic material was obtained during fieldwork carried out in 1994–2017. Herein the authors reconstruct the most significant moments in this investment from different points of view: the Roma and non-Roma neighbors. Each side interprets the fact in its own, rather paradoxical manner; each side has learned different new things in the process. The ambitious housing policy undoubtedly led to improvement of the Roma standard of living; it did not, however, increase the extent of their integration. The natural geology as well as manmade elements (e.g. a fence and a bridge) create and maintain boundaries. Nevertheless, analysis of the broader social context is decidedly more crucial than an analysis of facts. Ultimately, the sense of such publicly funded housing projects needs to be scrutinized from the diverse perspectives within the local community.